Validation of prognostic scoring systems for patients with metastatic renal cell carcinoma enrolled in phase I clinical trials. Issue 6 (23rd November 2020) - Hahn, Andrew W; Alhalabi, Omar; Msaouel, Pavlos; Meric-Bernstam, Funda; Naing, Aung; Jonasch, Eric; Piha-Paul, Sarina; Hong, David; Pant, Shubham; Yap, Timothy; Campbell, Erick; Le, Hung; et al.
Abstract : Background: For patients with metastatic renal cell carcinoma (mRCC) who progress on standard-of-care therapies, there is an unmet need for novel treatments. Phase I clinical trials are designed to test the safety, toxicity and optimal dosing of novel agents. Herein, we analysed the outcomes of patients with mRCC enrolled in phase I trials and assess the utility of prognostic scores. Methods: Patients with all histologies of mRCC were included if they received treatment on a phase I clinical trial at MD Anderson Cancer Center (MDACC). Survival outcomes were calculated using Cox proportional hazard model. Prognostic value of the International Metastatic RCC Database Consortium (IMDC), Royal Marsden Hospital (RMH) and MDACC scores was assessed using the likelihood ratio (LR) χ 2 test and the c-index. Results: Among 82 patients with mRCC who received treatment, 21 patients participated in more than one trial, resulting in 106 trial participants (TP). Median prior therapies was two. For all TPs, median overall survival (OS) was 31.2 months, progression-free survival (PFS) was 5.9 months and objective response rate was 22%. Median OS and PFS were significantly shorter with increasing IMDC, RMH and MDACC scores. The RMH and MDACC scores outperformed the IMDC score for predicting OS (RMH LR χ 2 =8.64; MDACC LR χ 2 =7.74; IMDC LR χ 2 =2.36) and PFS (RMH LR χ 2 =17.5; MDACC LR χ 2 =20.3; IMDC LR χ 2 =4.28). Conclusions: The RMH and MDACC prognostic scores can be used to predict OS for patients with mRCC in phase I trials and may guide patient selection. Patients with mRCC should be considered for phase I trials.